Immunohistochemical analysis of CD155 expression in triple-negative breast cancer patients. - Katsuhiro Yoshikawa (Public Library of Science (PLoS), 2021)
Introduction CD155 is an immune checkpoint protein. Its overexpression is an indicator of poor prognosis in some types of cancer. However, the significance of CD155 expression in patients with triple-negative breast cancer, and the relationship between CD155 and programmed death-ligand 1 (PD-L1) expression, have not yet been analyzed in detail. Methods Using immunohistochemical staining and tissue microarrays, we analyzed the expression profiles of CD155 and PD-L1 in 61 patients with triple-negative breast cancer. Relapse-free survival and overall survival rates were compared according to CD155 expression. The correlation between CD155 expression and clinicopathological factors, including PD-L1 expression (using SP142 and 73-10 assays), was also examined. Results CD155 expression was noted in 25 patients (41.0%) in this cohort. CD155 expression did not correlate with pathological stage, histological grade, Ki-67 labeling index, or stromal tumor-infiltrating lymphocytes. Only PD-L1 expression in tumor cells by SP142 assay significantly correlated with CD155 expression (p = 0.035); however, PD-L1 expression in tumor cells by 73-10 assay did not show a correlation (p = 0.115). Using the 73-10 assay, 59% of patients showed CD155 and/or PD-L1 expression in tumor cells. Moreover, using the SP142 assay, 63.3% of patients showed CD155 and/or PD-L1 expression in immune cells. CD155 expression did not correlate with either relapse-free survival or overall survival (p = 0.485 and 0.843, respectively). Conclusions CD155 may be a novel target for antitumor immunotherapy. The results of this study indicate that CD155 may expand the pool of candidates with triple-negative breast cancer who could benefit from antitumor immunotherapy.